Municipal climate vulnerability in Western Paraná (2012–2024): a multivariate approach to territorial planning - Piacentini, Rafael Venturin; Oliveira , Irene Carniatto (Sustainability in Debate, 2025)
This study investigates the occurrence of extreme weather events in municipalities of the Western mesoregion of Paraná, Brazil, between 2012 and 2024, using records from the State Civil Defence database. The adopted methodology involved multivariate statistical analysis using Principal Component Analysis (PCA), applied to data categorised into five event types: flash floods, flooding, heavy rainfall, gales, and hail. The results revealed distinct spatial patterns of municipal vulnerability, allowing the identification of groups of municipalities more prone to specific types of events. The proposed approach contributes to territorial planning and the formulation of public policies aimed at risk management and climate change adaptation.